Taxonomic distinctness in the diet of two sympatric marine turtle species. (6th August 2016) - Stringell, Thomas B.; Clerveaux, Wesley V.; Godley, Brendan J.; Kent, Flora E. A.; Lewis, Emma D. G.; Marsh, Jessica E.; Phillips, Quinton; Richardson, Peter B.; Sanghera, Amdeep; Broderick, Annette C.
Abstract: Marine turtles are considered keystone consumers in tropical coastal ecosystems and their decline through overexploitation has been implicated in the deterioration of reefs and seagrass pastures in the Caribbean. In the present study, we analysed stomach contents of green ( Chelonia mydas ) and hawksbill turtles ( Eretmochelys imbricata ) harvested in the legal turtle fishery of the Turks and Caicos Islands (Caribbean) during 2008–2010. Small juveniles to adult‐sized turtles were sampled. Together with data from habitat surveys, we assessed diet composition and the taxonomic distinctness (and other species diversity measures) in the diets of these sympatric marine turtle species. The diet of green turtles (n = 92) consisted of a total of 47 taxa: including three species of seagrass (present in 99% of individuals), 29 species of algae and eight sponge species. Hawksbill turtles (n = 45) consumed 73 taxa and were largely spongivorous (16 species; sponges present in 100% of individuals) but also foraged on 50 species of algae (present in 73% of individuals) and three species of seagrass. Plastics were found in trace amounts in 4% of green turtle and 9% of hawksbill turtle stomach samples. We expected to find changes in diet that might reflect ontogenetic shifts from small (oceanic‐pelagic) turtles to larger (coastal‐benthic) turtles. Dietary composition (abundance and biomass), however, did not change significantly with turtle size, although average taxonomic distinctness was lower in larger green turtles. There was little overlap in prey between the two turtle species, suggesting niche separation. Taxonomic distinctness routines indicated that green turtles had the most selective diet, whereas hawksbill turtles were less selective than expected when compared with the relative frequency and biomass of diet items. We discuss these findings in relation to the likely important trophic roles that these sympatric turtle species play in reef and seagrass habitats.